Remarkable solvent isotope dependence on gelation strength in low molecular weight hydro-gelators. Issue 10 (20th January 2017) - Canrinus, Tjalling R.; Cerpentier, Florian J. R.; Feringa, Ben L.; Browne, Wesley R.
Abstract : Hydrophobic/hydrophilic, π–π stacking, ionic and hydrogen bond formation interactions determine the strength of hydrogelators and here solvent deuteration and electrolyte strength impact gel melting heavily. Abstract : A delicate interplay of anisotropic hydrophobic/hydrophilic, π–π stacking, ionic and hydrogen bond interactions determine the strength of hydrogelators and are considered key factors in efforts to design potent small molecule hydrogelators. Here we show that solvent deuteration and electrolytic strength affect the strength of hydrogels formed from amino acid modified C 3 -symmetric cyclohexane trisamides profoundly. Gels formed by self-assembly through heating/cooling of solutions or by pH switching show up to a 30 °C increase in their melting temperatures in D2 O compared to H2 O. The unusually large solvent isotope effect on gel formation and thermal properties indicates that, in contrast to expectations, hydrogen bonding is not the primary determinant of gel strength but instead that hydrophobic interactions between the gelator molecules and the terminal carboxylic acid units are of greater importance. A conclusion that is supported by a similarly large effect of electrolytes on gel strength.